(3GdfXGe GdbGfhfj ddJCejfGJ hGdVeGf GdGLJeGYj aj GdeedcI GdYQHjI GdSYhOjI (B:s (3TQM CfXeI GdJCejfGJ GdGLJeGYjI, GdJCejf VO GdJYWd Yf GdYed, GdVeGf GdELJeGYj (B/s - (3GdYHO, QVG eMehOs ((3GdSYhOjI ;s (3eUQ (B:s (3OGQ GdELGOI WHGYI(B-(3fTQ(B-(3JhRjY,s, 2017)
(3jJfGhd cJGH (B((3GdfXGe GdbGfhfj ddJCejfGJ hGdVeGf GdGLJeGYj aj GdeedcI GdYQHjI GdSYhOjI (B: (3TQM CfXeI (B"(3GdJCejfGJ GdGLJeGYjI, GdJCejf VO GdJYWd Yf GdYed, GdVeGf GdELJeGYj(B") (3hGdPj bGe HJCdjag (B((3O(B. (3QVG eMeO GdYHO(B) (3aj MhGdj (B(319) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3bhGfjf GdJCejf GdGLJeGYj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdHGH GdChd eGgjI GdJCejfGJ GdGLJeGYjI, GdHGH GdKGfj CWQGa GdYdGbI GdJCejfjI, GdHGH GdKGdK aQhY GdJCejfGJ GdGLJeGYjI(B.s
(3GdeMJhjGJ (B: (3GdHGH GdChd (B: (3eGgjI GdJCejfGJ GdGLJeGYjI, GdaUd GdChd (B: (3eaghe GdJCejfGJ GdGLJeGYjI, GdaUd GdKGfj (B: (3GdJejjR Hjf GdJCejfGJ GdGLJeGYjI hGdCfXeI GdeTGHgI, GdaUd GdKGdK (B: (3JWhQ fXGe GdJCejfGJ GdGLJeGYjI aj GdeedcI GdYQHjI GdSYhOjI(B-(3GdHGH GdKGfj (B: (3CWQGa GdYdGbI GdJCejfjI, GdaUd GdChd (B: (3GdeDSSI GdYGeI ddJCejfGJ GdGLJeGYjI, GdaUd GdKGfj (B: (3UGMH GdYed, GdaUd GdKGdK (B: (3GdYGed, GdHGH GdKGdK (B: (3aQhY GdJCejfGJ GdGLJeGYjI, GdaUd GdChd (B: (3aQY GdCNWGQ GdegfjI, GdaUd GdKGfj (B: (3aQY GdeYGTGJ (B"(3GdTjNhNI hGdYLR hGdhaGI(B"-(3GdHGH GdQGHY (B: (3fXGe GdVeGf GdGLJeGYj aj GdeedcI, GdaUd GdChd (B: (3eGgjI GdVeGf GdGLJeGYj, GdaUd GdKGfj (B: (3CMcGe fXGe GdVeGf GdGLJeGYj aj GdeedcI(B.s
(3HHdjhLQGajI (B: (3UaMI (B307-312.s
Keywords: (3GdJCejf GdGLJeGYjs -- (3bhGfjf hJTQjYGJs -- (3GdSYhOjIs; (3GdJCejfs -- (3bhGfjf hJTQjYGJs -- (3GdSYhOjIs